Health status and health seeking behaviour in transgenders in Kakinada: a community based cross-sectional study - Veesam, Anantha Prakash; Bhimarasetty , Devi Madhavi; Vasireddy, Suhasini (International Journal Of Community Medicine And Public Health, 2023)
Background: Transgender (TG) is a term used to define individuals with a gender identity that is incongruent with the gender identity accorded to them at birth. Over the last two decades, health research on TGs has focused mainly on their sexual practices, leading to lack of information on their health problems and healthcare-seeking behaviour beyond STDs /HIV. The current study aimed to gain insight into the health status of TGs. Methods: A community based cross-sectional descriptive study was carried out in transgenders living in an urban area from December 2022 to January 2023 with a sample size of 160. Snowball sampling technique was used till the sample size was achieved. Data was collected using a pretested semi-structured questionnaire. Data was entered and analysed in MS Excel with descriptive statistics. Results: Majority of the study subjects belonged to 20-30 years of age. 43% were illiterates, 87% were living in rented houses. 89% screened for HIV in last 6 months, 57% underwent gender reassignment surgery. All study subjects gave history of suffering from STIs at least once, 11.9% were experienced STDs in past 1 year. 6.9% were tested positive for HIV and were on regular ART. 23.1% were diagnosed with anyone of NCD. First point care is contacting outreach worker in 58.8% of TGs. Conclusions: A more receptive attitude from the entire healthcare system is essential for improving the health status of this community. The inclusiveness promoted by universal health coverage will help each of these people’s health statuses improve.